Different treatment response to systemic corticosteroids according to white blood cell counts in severe COVID-19 patients. (31st December 2022) - Choi, Kwang Yong; Kim, Dong Hyun; Jin, Kwang Nam; Lee, Hyo Jin; Park, Tae Yun; Ryu, Borim; Lee, Jung-Kyu; Heo, Eun Young; Kim, Deog Kyeom; Lee, Hyun Woo
Abstract: Background: Limited data are available in COVID-19 patients on the prediction of treatment response to systemic corticosteroid therapy based on systemic inflammatory markers. There is a concern whether the response to systemic corticosteroid is different according to white blood cell (WBC) counts in COVID-19 patients. We aimed to assess whether WBC count is related with the clinical outcomes after treatment with systemic corticosteroids in severe COVID-19. Methods: We conducted a retrospective cohort study and analysed the patients hospitalised for severe COVID-19 and received systemic corticosteroids between July 2020 and June 2021. The primary endpoint was to compare the composite poor outcome of mechanical ventilation, extracorporeal membrane oxygenation, and mortality among the patients with different WBC counts. Results: Of the 585 COVID-19 patients who required oxygen supplementation and systemic corticosteroids, 145 (24.8%) belonged to the leukopoenia group, 375 (64.1%) belonged to the normal WBC group, and 65 (11.1%) belonged to the leukocytosis group. In Kaplan-Meier curve, the composite poor outcome was significantly reduced in leukopoenia group compared to leukocytosis group (log-rank p -value < 0.001). In the multivariable Cox regression analysis, leukopoenia group was significantly associated with a lower risk of the composite poor outcome compared to normal WBC group (adjusted hazard ratio [aHR] = 0.32, 95% CI 0.14–0.76, p -value = 0.009) and leukocytosis group (aHR = 0.30, 95% CI = 0.12–0.78, p -value = 0.013). There was no significant difference in aHR for composite poor outcome between leukocytosis and normal WBC group. Conclusion: Leukopoenia may be related with a better response to systemic corticosteroid therapy in COVID-19 patients requiring oxygen supplementation. KEY MESSAGES: In severe COVID-19 treated with systemic corticosteroids, patients with leukopoenia showed a lower hazard for composite poor outcome compared to patients with normal white blood cell counts or leukocytosis. Leukopoenia may be a potential biomarker for better response to systemic corticosteroid therapy in COVID-19 pneumonia.